Inorganic composition article and crystallized glass

The inorganic composition article with α-cristobalite as a main crystal phase and specific oxide content achieves high surface compressive stress, addressing the hardness and strength issues of existing materials for electronic and automotive applications.

JP7600089B2Active Publication Date: 2024-12-16OHARA INC

Patent Information

Application Number
JP2021199770
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-03-06
Filing Date
2021-12-09
Publication Date
2024-12-16
Estimated Expiration
2040-03-05

AI Technical Summary

Technical Problem

Existing inorganic materials used for protecting electronic device displays and automotive lenses lack sufficient hardness and surface compressive stress values, making them unsuitable for harsh environments.

Method used

An inorganic composition article comprising α-cristobalite or α-cristobalite solid solution as a main crystal phase, with specific oxide content ratios of SiO2, Li2O, Al2O3, ZrO2, and other components, achieving a surface compressive stress value of 600 MPa or more.

Benefits of technology

The composition provides high surface hardness and mechanical strength, enabling effective protection in harsh environments for electronic devices and automotive components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007600089000001
    Figure 0007600089000001
  • Figure 0007600089000002
    Figure 0007600089000002
  • Figure 0007600089000003
    Figure 0007600089000003
Patent Text Reader

Abstract

Provided are an inorganic composition article and crystallized glass having high surface hardness. [Solution] The inorganic composition article contains, as a main crystalline phase, one or more selected from α-cristobalite and α-cristobalite solid solution, and has, in mass % oxide equivalent, an SiO2 component content of 50.0% to 75.0%, a Li2O component content of 3.0% to 10.0%, an Al2O3 component content of 5.0% or more but less than 15.0%, and a total content of Al2O3 component and ZrO2 component of 10.0% or more, and has a surface compressive stress value of 600 MPa or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an inorganic composition article having a hard surface. 、 and , hard, and capable of achieving high compressive stress values ​​on the surface This relates to glass-ceramics.

[0002] Various inorganic materials are expected to be used as cover glass and housings for protecting displays of mobile electronic devices such as smartphones and tablet PCs, as protectors for protecting lenses of in-vehicle optical devices, as interior bezels and console panels, touch panel materials, smart keys, etc. These devices are required to be used in harsher environments than those required for hard disk substrates, and there is an increasing demand for inorganic materials with higher hardness.

[0003] Glass with increased strength is called glass-ceramic. Glass-ceramic is made by precipitating crystals inside glass, and is known to have superior mechanical strength to amorphous glass.

[0004] On the other hand, chemical strengthening is known as a method for increasing the strength of glass. By exchanging and reacting the alkali components present in the surface layer of the glass with alkali components having a larger ionic radius, a compressive stress layer is formed on the surface, which can suppress the progression of cracks and increase the mechanical strength. To achieve this, it is necessary to obtain a sufficiently high compressive stress value.

[0005] Patent Document 1 discloses an inorganic composition article for information recording media that can be chemically strengthened. It is stated that the α-cristobalite-based inorganic composition article described in Patent Document 1 can be chemically strengthened and can be used as a material substrate with high strength. However, crystallized glass for information recording media, such as substrates for hard disks, is not intended for use in harsh environments, and no discussion has been made about the surface compressive stress value associated with chemical strengthening. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent Publication No. 2008-254984 Summary of the Invention

[0007] The object of the present invention is to provide an inorganic composition article having a high surface hardness. 、 and , hard, and capable of achieving high compressive stress values ​​on the surface The object of the present invention is to provide a crystallized glass.

[0008] The present invention provides the following: (Configuration 1) An inorganic composition article containing one or more types selected from α-cristobalite and α-cristobalite solid solution as a main crystalline phase, In terms of oxide, mass % SiO 2 Ingredient content is 50.0%~75.0%, Li 2 O content is 3.0% to 10.0%, Al 2 O 3 The content of the ingredient is 5.0% or more but less than 15.0%. Al 2 O 3 Composition and ZrO 2 The total content of the ingredients is 10.0% or more, Surface compressive stress value is 600MPa or more The inorganic composition article. (Configuration 2) In terms of oxide, mass % ZrO 2 The content of the ingredient is more than 0% and less than 10.0%. K 2 O content is 0% to 10.0%, P 2 O 5 Ingredient content: 0%~10.0% 2. The inorganic composition article according to claim 1, (Configuration 3) In terms of oxide, mass % Na 2 O content is 0% to 10.0%, MgO content: 0%~10.0%, CaO content is 0%~10.0%, SrO content: 0%~10.0%, BaO content is 0%~10.0%, ZnO content is 0% to 10.0%, Sb 2 O 3 Ingredient content: 0%~3.0% 3. The inorganic composition article according to claim 1 or 2, (Configuration 4) In terms of oxide, mass % Nb 2 O 5 Ingredient content: 0%~10.0%, Ta 2 O 5 Ingredient content: 0%~10.0%, TiO 2 Ingredient content is between 0% and 7.0% 4. The inorganic composition article according to any one of configurations 1 to 3, (Configuration 5) The glass-ceramics contain, as a main crystal phase, one or more selected from α-cristobalite and α-cristobalite solid solution, In terms of oxide, mass % SiO 2 Ingredient content is 50.0%~75.0%, Li 2 O content is 3.0% to 10.0%, Al 2 O 3 The content of the ingredient is 5.0% or more but less than 15.0%. ZrO 2 The content of the ingredient is more than 0% and less than 10.0%. Al 2 O 3 Composition and ZrO 2 The total content of ingredients is 10.0% or more This is glass-ceramics. (Configuration 6) In terms of oxide, mass % K 2 O content is 0% to 5.0%. P 2 O 5Ingredient content: 0%~10.0% 6. The crystallized glass according to claim 5, (Configuration 7) In terms of oxide, mass % Na 2 O content is 0% to 4.0%, MgO content is 0%~4.0%, CaO content is 0%~4.0%. SrO content is 0%~4.0%, BaO content is 0%~5.0%, ZnO content is 0% to 10.0%, Sb 2 O 3 Ingredient content: 0%~3.0% 7. The crystallized glass according to claim 5 or 6, (Configuration 8) In terms of oxide, mass % Nb 2 O 5 Ingredient content: 0%~5.0% Ta 2 O 5 Ingredient content: 0%~6.0% TiO 2 Ingredient content is between 0% and 1.0% 8. The crystallized glass according to any one of configurations 5 to 7, wherein

[0009] According to the present invention, an inorganic composition article having high surface hardness is provided. 、 and , hard, and capable of achieving high compressive stress values ​​on the surface It is possible to provide crystallized glass.

[0010] The inorganic composition article and crystallized glass of the present invention can be used as protective materials for devices, etc., taking advantage of the fact that they are inorganic materials with high strength. They can be used as cover glass or housings for smartphones, or as components for portable electronic devices such as tablet PCs and wearable terminals, or as components for protective protectors and head-up display substrates used in transport vehicles such as cars and airplanes. They can also be used for other electronic devices and machinery, building materials, solar panel components, projector components, and cover glass (windshield) for glasses and watches. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, embodiments and examples of the inorganic composition article of the present invention will be described in detail. However, the present invention is not limited to the following embodiments and examples in any way, and can be practiced with appropriate modifications within the scope of the object of the present invention.

[0012] The inorganic composition article of the present invention is an inorganic composition article containing, as a main crystal phase, one or more selected from α-cristobalite and α-cristobalite solid solution, In terms of oxide, mass % SiO 2 Ingredient content is 50.0%~75.0%, Li 2 O content is 3.0% to 10.0%, Al 2 O 3 The content of the ingredient is 5.0% or more but less than 15.0%. Al 2 O 3 Composition and ZrO 2 The total content of the ingredients is 10.0% or more, The surface compressive stress value is 600 MPa or more. By having this predominant crystalline phase, composition and compressive stress value, a hard inorganic composition article can be obtained.

[0013] The "inorganic composition article" in the present invention is composed of an inorganic composition material such as glass, crystallized glass, ceramics, or a composite material thereof. The article of the present invention includes, for example, an article obtained by forming these inorganic materials into a desired shape by processing or synthesis through chemical reaction. In addition, a green compact obtained by crushing an inorganic material and then pressing it, or a sintered body obtained by sintering the green compact, etc., are also included. The shape of the article obtained here is not limited by smoothness, curvature, size, etc. For example, it may be a plate-shaped substrate, a molded body having a curvature, or a three-dimensional structure having a complex shape.

[0014] The crystallized glass of the present invention is a crystallized glass containing, as a main crystal phase, at least one selected from α-cristobalite and α-cristobalite solid solution, In terms of oxide, mass % SiO 2 Ingredient content is 50.0%~75.0%, Li 2 O content is 3.0% to 10.0%, Al 2 O 3 The content of the ingredient is 5.0% or more but less than 15.0%. ZrO 2 The content of the ingredient is more than 0% and less than 10.0%. Al 2 O 3 Composition and ZrO 2 The total content of ingredients is 10.0% or more It is. By having this main crystal phase and composition, it is possible to obtain a crystallized glass which is hard and capable of achieving a high compressive stress value on the surface.

[0015] Glass-ceramics, also known as glass ceramics, are materials in which crystals are precipitated inside glass by heat-treating the glass. Glass-ceramics are materials that have a crystalline phase and a glass phase, and are distinguished from amorphous solids. In general, the crystalline phase of glass-ceramics is identified using the angle of the peaks that appear in the X-ray diffraction pattern of X-ray diffraction analysis.

[0016] The inorganic composition article and crystallized glass (hereinafter, also simply referred to as the inorganic composition article) of the present invention will be described below. The inorganic composition article is preferably reinforced crystallized glass. The inorganic composition article contains at least one selected from α-cristobalite and α-cristobalite solid solution as a main crystal phase. The inorganic composition article in which these crystal phases are precipitated has high mechanical strength. Here, the term "main crystalline phase" in this specification corresponds to the crystalline phase contained most abundantly in the inorganic composition article, as determined from the peaks in the X-ray diffraction pattern.

[0017] In this specification, the content of each component is expressed in mass% converted to oxide unless otherwise specified. Here, "oxide conversion" refers to the amount of oxide of each component contained in the inorganic composition product expressed in mass% when the total mass of the oxide is 100 mass% when all the constituent components of the inorganic composition product are decomposed and converted to oxide. In this specification, A% to B% means A% or more and B% or less.

[0018] SiO 2 The component is an essential component necessary for forming one or more selected from α-cristobalite and α-cristobalite solid solution. The upper limit is preferably 75.0% or less, less than 74.0%, less than 73.7%, less than 72.5%, or less than 72.0%. The lower limit is preferably 50.0% or more, 55.0% or more, 58.0% or more, 60.0% or more, 62.0% or more, or 64.0% or more.

[0019] Li 2 The O component is an important component for improving the meltability of the raw inorganic composition. If the amount is less than 3.0%, the above effect is not obtained and melting of the raw glass becomes difficult. If the amount exceeds 10.0%, the formation of lithium disilicate crystals increases. The lower limit is preferably 3.0% or more, 3.5% or more, 4.0% or more, 4.5% or more, 5.0% or more, or 5.5% or more, and the upper limit is preferably 10.0% or less, 9.0% or less, 8.5% or less, or 8.0% or less.

[0020] Al 2 O 3 The component is suitable for improving the mechanical strength of an inorganic composition article. The upper limit is preferably less than 15.0%, 14.5% or less, 14.0% or less, 13.5% or less, or 13.0% or less. The lower limit is preferably 5.0% or more, 5.5% or more, 5.8% or more, 6.0% or more, or 6.5% or more.

[0021] ZrO 2 The component is an optional component that can be added to improve mechanical strength. The upper limit is preferably 10.0% or less, 9.5% or less, 9.0% or less, 8.8% or less, or 8.5% or less. The lower limit is preferably more than 0%, 0.1% or more, 1.0% or more, 1.5% or more, 1.8% or more, or 2.0% or more.

[0022] Al 2 O 3 Composition and ZrO 2 The sum of the contents of the components [Al 2 O 3 +ZrO 2 If the content of [Al] is large, the compressive stress on the surface increases when chemical strengthening, heat treatment strengthening, or ion implantation strengthening is performed. 2 O 3 +ZrO 2 ] The lower limit is 10.0% or more, 10.5% or more, 11.0% or more, 12.0% or more, 13.0% or more, or more than 13.5%. On the other hand, [Al 2 O 3 +ZrO 2 The upper limit of] is preferably 22.0% or less, 21.0% or less, 20.0% or less, or 19.0% or less.

[0023] SiO 2 Ingredients, Li 2 O component, Al 2 O 3 Composition and ZrO 2 The lower limit of the total content of the components can be 75.0% or more, 80.0% or more, 83.0% or more, or 85.0% or more.

[0024] P 2 O 5 The component is an optional component that can be added to act as a crystal nucleation agent for the inorganic composition. The upper limit is preferably 10.0% or less, 9.0% or less, 8.0% or less, or 7.5% or less. The lower limit is preferably 0% or more, 0.5% or more, 1.0% or more, or 1.5% or more.

[0025] K 2 The O component is an optional component that can be added to improve the surface compressive stress, and the lower limit can be preferably set to 0% or more, 0.1% or more, 0.3% or more, 0.5% or more, or 0.8% or more. Moreover, if it is contained in excess, crystal precipitation may become difficult in some cases. Therefore, the upper limit can be preferably set to 10.0% or less, 6.0% or less, 5.0% or less, 4.0% or less, 3.5% or less, or 3.0% or less.

[0026] Na 2 The O component is an optional component that can be added to improve the surface compressive stress. If it is contained in excess, it may be difficult to obtain the desired crystal phase. The upper limit can be preferably set to 10.0% or less, 5.0% or less, 4.0% or less, 3.0% or less, or 2.5% or less.

[0027] The MgO, CaO, SrO, BaO, and ZnO components are optional components and improve the melting property of the inorganic composition, but if they are contained in excess, the resulting crystals tend to become coarse. Therefore, the MgO component is preferably set to an upper limit of 10.0% or less, 7.0% or less, 5.0% or less, 4.0% or less, 3.0% or less, or 2.5% or less. The CaO component is preferably set to an upper limit of 10.0% or less, 7.0% or less, 5.0% or less, 4.0% or less, 3.0% or less, or 2.0% or less. The SrO component is preferably set to an upper limit of 10.0% or less, 7.0% or less, 4.0% or less, 3.0% or less, 2.5% or less, or 2.3% or less. The BaO component is preferably set to an upper limit of 10.0% or less, 8.0% or less, 7.0% or less, 6.0% or less, 5.0% or less, or 4.0% or less. The upper limit of the ZnO component can be preferably set to 10.0% or less, 9.0% or less, 8.8% or less, 8.5% or less, 8.0% or less, or 7.5% or less.

[0028] The total amount of SrO and BaO components is preferably less than 12.0%, and more preferably, the upper limit can be set to less than 10.0%, less than 8.0%, less than 6.0%, or 4.5% or less.

[0029] The inorganic composition article may contain Nb 2 O 5 Ingredients, Ta 2 O 5 Ingredients: TiO 2 Each of the components may or may not be included. 2 O 5 The upper limit of the component can be preferably set to 10.0% or less, 6.0% or less, 5.0% or less, or 3.0% or less. 2 O 5 The TiO component can preferably have an upper limit of 10.0%, 8.0%, 6.0%, or 4.0%. 2 The upper limit of the component can be preferably less than 7.0%, 5.0% or less, 3.0% or less, 2.0% or less, less than 1.0%, 0.5% or less, or 0.1% or less.

[0030] In addition, the inorganic composition article may be B within a range that does not impair the effects of the present invention. 2 O3 Ingredients, La 2 O 3 Component, Y 2 O 3 Ingredients: WO 3 Ingredients, TeO 2 Ingredients: Bi 2 O 3 The amount of each of the components may be 0% to 2.0%, 0% or more and less than 2.0%, or 0% to 1.0%.

[0031] Furthermore, the inorganic composition article may or may not contain other components not described above, as long as the properties of the inorganic composition article of the present invention are not impaired. For example, metal components such as Gd, Yb, Lu, V, Cr, Mn, Fe, Co, Ni, Cu, Ag, and Mo (including oxides of these metals) may be included.

[0032] Sb as a glass fining agent 2 O 3 The upper limit of the content is preferably 3.0% or less, more preferably 1.0% or less, and further preferably 0.6% or less.

[0033] Sb is also used as a fining agent for glass. 2 O 3 In addition to the ingredients, SnO 2 Ingredients: CeO 2 Component, As 2 O 3 The fining agent may contain one or more selected from the group consisting of F, NOx, and SOx, or may not contain any of these. However, the upper limit of the content of the fining agent is preferably 3.0% or less, more preferably 1.0% or less, and most preferably 0.6% or less.

[0034] On the other hand, since there has been a tendency in recent years to refrain from using Pb, Th, Tl, Os, Be, Cl and Se as harmful chemical substances, it is preferable that the material is substantially free of these components.

[0035] The inorganic composition article of the present invention has a compressive stress layer formed on its surface with a compressive stress value CS (MPa) of 600 MPa or more. The crystallized glass of the present invention can also form a compressive stress layer on its surface. The compressive stress value of the compressive stress layer is preferably 600 MPa or more, more preferably 650 MPa or more, even more preferably 680 MPa or more, and particularly preferably 700 MPa or more. The upper limit is, for example, 1400 MPa or less, 1300 MPa or less, 1200 MPa or less, or 1100 MPa or less. By having such a compressive stress value, it is possible to suppress the progression of cracks and increase mechanical strength.

[0036] The thickness DOLzero (μm) of the compressive stress layer is not limited because it depends on the thickness of the inorganic composition article, but for example, in the case of a crystallized glass substrate having a thickness of 10 mm, the lower limit of the thickness of the compressive stress layer can be 1 μm or more, 30 μm or more, 50 μm or more, 70 μm or more, 100 μm or more, 130 μm or more, 150 μm or more, 180 μm or more, or 200 μm or more.

[0037] For example, when the inorganic composition article is a crystallized glass substrate, the article can be produced by the following method: the raw materials are mixed uniformly so that the above-mentioned components are within the prescribed content range, and the mixture is melt-molded to produce raw glass, which is then crystallized to produce crystallized glass.

[0038] The heat treatment for crystal precipitation may be a one-stage or two-stage heat treatment. In the two-stage heat treatment, a nucleation step is first performed by heat treatment at a first temperature, and after this nucleation step, a crystal growth step is performed by heat treatment at a second temperature higher than that of the nucleation step. The first temperature of the two-stage heat treatment is preferably 450° C. to 750° C., more preferably 500° C. to 720° C., and further preferably 550° C. to 680° C. The holding time at the first temperature is preferably 30 minutes to 2000 minutes, and more preferably 180 minutes to 1440 minutes. The second temperature of the two-stage heat treatment is preferably 600° C. to 800° C., more preferably 650° C. to 750° C. The holding time at the second temperature is preferably 30 minutes to 600 minutes, more preferably 60 minutes to 400 minutes. In one-stage heat treatment, the nucleation process and the crystal growth process are carried out consecutively at a single temperature. Usually, the temperature is raised to a predetermined heat treatment temperature, and after reaching the heat treatment temperature, the temperature is maintained for a certain period of time, and then the temperature is lowered. When the heat treatment is performed at one temperature step, the heat treatment temperature is preferably 600° C. to 800° C., more preferably 630° C. to 770° C. The holding time at the heat treatment temperature is preferably 30 minutes to 500 minutes, more preferably 60 minutes to 400 minutes.

[0039] A glass molded body can be produced from the crystallized glass by, for example, grinding and polishing means, etc. The glass molded body can be processed into a thin plate to produce a crystallized glass substrate.

[0040] Methods for forming a compressive stress layer in an inorganic composition article and in a crystallized glass without a compressive stress layer include, for example, a chemical strengthening method in which an alkali component present in the surface layer of a crystallized glass substrate is subjected to an exchange reaction with an alkali component having a larger ionic radius to form a compressive stress layer in the surface layer, a thermal strengthening method in which a crystallized glass substrate is heated and then rapidly cooled, and an ion implantation method in which ions are implanted into the surface layer of a crystallized glass substrate.

[0041] The chemical strengthening method can be carried out, for example, by the following steps: A crystallized glass base material is dissolved in a salt containing potassium or sodium, such as potassium nitrate (KNO 3 ), sodium nitrate (NaNO 3 The treatment of contacting or immersing in the molten salt (chemical strengthening treatment) may be carried out in one step or two steps.

[0042] For example, in the case of a two-stage chemical strengthening treatment, first, the steel is contacted with or immersed in a sodium salt or a mixed salt of potassium and sodium heated at 350°C to 550°C for 1 to 1440 minutes, preferably 90 to 500 minutes, followed by contacting with or immersing in a potassium salt or a mixed salt of potassium and sodium heated at 350°C to 550°C for 1 to 1440 minutes, preferably 60 to 600 minutes. In the case of one-stage chemical strengthening treatment, the material is brought into contact with or immersed in a salt containing potassium or sodium, or a mixed salt thereof, heated at 350°C to 550°C for 1 to 1,440 minutes.

[0043] Chemical strengthening of inorganic composition articles may be performed in one step or multiple steps. However, in order to efficiently increase the surface compressive stress and increase the thickness of the compressive stress layer, a two-step strengthening process is preferred, in which first, strengthening is performed with a molten salt of sodium, and then, second, strengthening is performed with a molten salt of potassium.

[0044] The thermal strengthening method is not particularly limited, but for example, the inorganic composition article base material is heated to 300°C to 600°C, and then rapidly cooled by water cooling and / or air cooling, so that a compressive stress layer can be formed due to the temperature difference between the surface and the inside of the glass substrate. In addition, by combining with the above-mentioned chemical treatment method, the compressive stress layer can be formed more effectively.

[0045] The ion implantation method is not particularly limited, but for example, any ion is bombarded with the surface of the inorganic composition article base material at an acceleration energy and acceleration voltage that are not enough to destroy the surface of the base material, thereby implanting ions into the surface of the base material. By subsequently carrying out a heat treatment as necessary, a compressive stress layer can be formed on the surface in the same manner as in other methods. EXAMPLES

[0046] Examples 1 to 28, Comparative Examples 1 and 2 As raw materials for each component of the crystallized glass, the corresponding oxides, hydroxides, carbonates, nitrates, fluorides, chlorides, metaphosphate compounds, etc. were selected, and these raw materials were weighed out and mixed uniformly to obtain the compositions shown in Tables 1 to 3.

[0047] Next, the mixed raw materials were put into a platinum crucible and melted in an electric furnace at 1300°C to 1600°C for 2 to 24 hours depending on the melting difficulty of the glass composition. After that, the molten glass was stirred to homogenize it, and then the temperature was lowered to 1000°C to 1450°C, and then it was poured into a mold and slowly cooled to produce raw glass. In Examples 1 to 24 and Comparative Examples 1 and 2, the obtained raw glass was crystallized by a two-stage heat treatment to produce crystallized glass. In the first stage, nucleation was performed at the temperature and time shown in the "nucleation conditions" in Tables 1 to 3, and in the second stage, crystallization was performed at the temperature and time shown in the "crystallization conditions" in Tables 1 to 3. In Examples 25 to 28, the raw glass was crystallized by a one-stage heat treatment to produce crystallized glass. Nucleation was performed and crystallization was performed at the temperature and time shown in the "crystallization conditions" in Table 3.

[0048] The crystal phases of the crystallized glasses of Examples 1 to 28 and Comparative Examples 1 and 2 were determined from the angles of peaks appearing in X-ray diffraction patterns obtained using an X-ray diffraction analyzer (D8Dsicover, manufactured by Bruker). When the X-ray diffraction patterns of the crystallized glasses of Examples 1 to 28 and Comparative Examples 1 and 2 were examined, all of them showed a main peak (the peak with the highest intensity and the largest peak area) at a position corresponding to the peak pattern of α-cristobalite and / or α-cristobalite solid solution, and therefore it was determined that α-cristobalite and α-cristobalite solid solution had precipitated as the main crystal phase in all of them.

[0049] The produced crystallized glass was cut and ground, and then polished parallel to each other to a thickness of 10 mm to obtain a crystallized glass substrate. Next, in Examples 1 to 23, 25, and 26, the crystallized glass substrate was used as a base material and strengthened in two stages to obtain a chemically strengthened crystallized glass substrate. Specifically, NaNO 3 After immersion in molten salt (first step), the specimens were heated with KNO at the temperatures and times shown in Tables 1 to 3. 3 The substrates obtained in Example 24 and Comparative Examples 1 and 2 were immersed in molten salt at the temperatures and times shown in Table 3. 3The strengthened substrates of Comparative Examples 1 and 2 were chemically strengthened crystallized glass substrates corresponding to Examples 25 and 27 described in Patent Document 1. The substrates obtained in Examples 27 and 28 were immersed in molten salt and strengthened in one step. 3 It was strengthened by immersing it in molten salt.

[0050] The surface compressive stress value (CS) of the thus obtained reinforced crystallized glass was measured. In Examples 1 to 26 and Comparative Examples 1 and 2, a glass surface stress meter FSM-6000LE series manufactured by Orihara Manufacturing Co., Ltd. was used, and in Examples 27 and 28, a scattered light photoelastic stress meter SLP-1000 was used. As shown in Tables 1 to 3, in the FSM-6000LE series, a light source with a wavelength of 596 nm or 365 nm was selected as the light source of the measuring device according to the reinforcement depth. In the SLP-1000, a light source with a wavelength of 640 nm was used for the measurement.

[0051] The refractive index values ​​used as CS measurement conditions are shown in Tables 1 to 3. The refractive index used in CS measurement was the refractive index value at the wavelength (640 nm, 596 nm, or 365 nm) of the light source used in the measurement. The refractive index value at a specified wavelength was calculated using a quadratic approximation formula from the measured refractive index values ​​at the wavelengths of C line, d line, F line, and g line in accordance with the V-block method specified in JIS B 7071-2:2018.

[0052] The values ​​of the photoelastic constant, which are the CS measurement conditions, were used as shown in Tables 1 to 3. The photoelastic constant used in the CS measurement was the value of the photoelastic constant at the wavelength (640 nm, 596 nm, or 365 nm) of the light source used in the measurement. The photoelastic constant at wavelengths of 640 nm, 596 nm, or 365 nm was calculated using a quadratic approximation formula from the measured values ​​of the photoelastic constant at wavelengths of 435.8 nm, 546.1 nm, and 643.9 nm.

[0053] The photoelastic constant (β) was measured by polishing the specimen on both sides to form a disk shape with a diameter of 25 mm and a thickness of 8 mm, applying a compressive load in a specified direction, measuring the optical path difference generated at the center of the glass, and calculating it using the relational formula δ=β·d·F. In the above formula, the optical path difference is expressed as δ (nm), the glass thickness as d (cm), and the stress as F (MPa).

[0054] In measuring the depth DOLzero (μm) (also called stress depth) when the compressive stress of the compressive stress layer is 0 MPa, the sensitivity of the device differs depending on the depth of DOLzero (μm), so a measuring device was selected according to the depth. The depth measurements for Examples 1 to 23 and 25 to 28 were performed using a scattered light photoelastic stress meter SLP-1000, and for Example 24 and Comparative Examples 1 and 2, a glass surface stress meter FSM-6000LE series manufactured by Orihara Manufacturing was used. The wavelength of the measurement light source, the refractive index of the sample, and the photoelastic constant were calculated using the values ​​shown in the table. However, when DOLzero (μm) exceeds 500 μm, it is not possible to measure with the above measuring device, so it is described as >500.

[0055] The results are shown in Tables 1 to 3. It is clear from Tables 1 to 3 that the inorganic composition article (crystallized glass) of the present invention has a high compressive stress layer in the surface of CS and is hard.

[0056] [Table 1]

[0057] [Table 2]

[0058] [Table 3]

[0059] Although some embodiments and / or examples of the present invention have been described in detail above, those skilled in the art can easily make many modifications to these exemplary embodiments and / or examples without substantially departing from the novel teachings and advantages of the present invention, and therefore many such modifications are within the scope of the present invention. The contents of all references cited in this specification are incorporated herein by reference in their entirety.

Claims

1. The glass-ceramics contain, as a main crystal phase, one or more selected from α-cristobalite and α-cristobalite solid solution, In terms of oxide, mass % SiO 2 The content of the ingredient is 50.0% to 75.0%, Li 2 The content of O component is 3.0% to 10.0%. A 2 O 3 The content of the ingredient is 10.5% or more but less than 15.0%; ZrO 2 The content of the ingredient is more than 0% and 10.0% or less, A 2 O 3 Ingredients and ZrO 2 The total content of ingredients is more than 10.5% This is glass-ceramics.

2. The glass-ceramics contain, as a main crystal phase, one or more selected from α-cristobalite and α-cristobalite solid solution, In terms of oxide, mass % SiO 2 The content of the ingredient is 50.0% to 75.0%, Li 2 The content of O component is 3.0% to 10.0%. A 2 O 3 The content of the ingredient is 5.0% or more and less than 15.0%; ZrO 2 The content of the ingredient is more than 0% and 10.0% or less, The content of As 2 O 3 component is 0.6% or less, A 2 O 3 Ingredients and ZrO 2 The total content of ingredients is 14.5% or more This is glass-ceramics.

3. In terms of oxide, mass % K 2 O content: 0% to 5.0% P 2 O 5 Ingredient content: 0% to 10.0% 3. The crystallized glass according to claim 1 or 2, wherein

4. In terms of oxide, mass % Na 2 O content is 0% to 4.0%, The content of MgO component is 0% to 4.0%, The content of CaO component is 0% to 4.0%, The content of SrO component is 0% to 4.0%. The content of BaO component is 0% to 5.0%, ZnO content is 0% to 10.0%, Sb 2 O 3 Ingredient content: 0% to 3.0% 4. The crystallized glass according to claim 1, wherein

5. In terms of oxide, mass % Nb 2 O 5 The content of the ingredient is 0% to 5.0%, T 2 O 5 The content of the ingredient is 0% to 6.0%, TiO 2 Ingredient content is between 0% and 1.0% 5. The crystallized glass according to claim 1, wherein

Citation Information

Patent Citations

  • Glass ceramic substrate for information storage medium

    JP2000233941A

  • Glass substrate material for information memory medium and method for processing glass ceramic substrate material

    JP2000339672A

  • Glass ceramics for cathode-ray tube(CRT)

    JP2001035417A

  • Glass ceramic

    JP2002097037A

  • Crystallized glass substrate for information recording medium

    JP2002145639A

Cited By

  • Reinforced crystallized glass

    JPWO2022050105A1